1974
DOI: 10.1128/jb.119.1.282-293.1974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen and Glucose on Energy Metabolism and Dimorphism of Mucor genevensis Grown in Continuous Culture: Reversibility of Yeast-Mycelium Conversion

Abstract: Mucor genevensis was grown in both glucose-limited and glucose-excess continuous cultures over a range of dissolved oxygen concentrations (<0.1 to 25 ,uM) to determine the effects of glucose and the influence of metabolic mode (fermentative versus oxidative) on dimorphic transformations in this organism. The extent of differentiation between yeast and mycelial phases has been correlated with physiological and biochemical parameters of the cultures. Under glucose limitation, oxidative metabolism increased as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
4
19
0
1
Order By: Relevance
“…We conclude from these observations that in Mucor the morphological conversion of yeast to mycelia can occur without a radical change in catabolic carbon metabolism. This observation is consistent with the earlier observations of Paznokas and Sypherd (12) and Rogers et al (13). The study reported here also shows that the yeast form is consistently correlated with a high flux of glucose carbon through the EMP and PP pathways, whereas the mycelial form does not show a consistent pattern in catabolic carbon metabolism.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We conclude from these observations that in Mucor the morphological conversion of yeast to mycelia can occur without a radical change in catabolic carbon metabolism. This observation is consistent with the earlier observations of Paznokas and Sypherd (12) and Rogers et al (13). The study reported here also shows that the yeast form is consistently correlated with a high flux of glucose carbon through the EMP and PP pathways, whereas the mycelial form does not show a consistent pattern in catabolic carbon metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, these aerobic yeast cells continued to produce ethanol and carbon dioxide at a rate indicative of a fermentative metabolism. These workers (13) concluded that respiratory capacity was not correlated with morphology. In addition, Paznokas and Sypherd (12) measured the respiratory capacity of aerobic mycelia and aerobic dbcAMP-treated yeast and concluded that morphology was independent of respiratory capacity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The numbered proteins are discussed in the text. laboratories (5,10,12). Other metabolic events requiring molecular oxygen might be important to mycelial development.…”
Section: Discussionmentioning
confidence: 99%
“…The Mucorales contains a number of species that are known to undergo this dual morphogenetic change. They include the much-researched Mucor rouxii (Bartnicki-Garcia, 1968;Bartnicki-Garcia and Nickerson, 1962a, b, c, d;Schulz et al, 1974), Mucor circinelloides (Lubberhusen et al, 2003;McIntyre et al, 2002), Mucor genevensis (Rogers et al, 1974), Mucor racemosus (Mooney and Sypherd, 1976), Mucor pusillus (Fisher, 1977), Mucor hiemalis (Mysyakina and Funtikova, 2000), Cokeromyces poitrasii (Price et al, 1973), Mycotypha spp. (Hall and Kolankaya, 1974).…”
Section: Introductionmentioning
confidence: 99%